Peran Guru Agama Dalam Upaya Eksternalisasi Nilai Budaya Lokal dan Keagamaan di Sekolah - Sari, Novita; Jamilah, , Syarifah Ainun; Rahman, Mujibur; Bokay, Novisius Bivarelly (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2021)
Schools have an important role in introducing religious values ​​and local cultural values ​​to their students so that later they can become wise human beings. The purpose of this study was to see how the role of religious teachers in efforts to externalize local cultural and religious values ​​in schools. This study uses a qualitative method with an Appreciative Inquiry approach. The results show that there is a unified value of dhamma taught by Buddhism, verses of the Qur'an which are guided by Islam, and articles in the new covenant that are believed by Christianity, which imply mutual respect, respect, and love. between fellow human beings who are equally recommended by these religions and do not forget to also syncretize local cultural values ​​which are also taught and become the main support or basis of the character education curriculum offered by schools in instilling universal values ​​from religion and culture such as mappatabe ', lempu, getteng, sipakatau, there are tongeng, barani, macca, makkareso, siri', and pacce. These values ​​were successfully externalized by the school together with the teachers to all students in the school in the form of annual activities such as Independence Day Celebration, Art Day, Mother's Day, End Year Celebration and Christmas Day, Chinese New Year Celebration, Iftar. together, graduation day, open house/tea time and religion day.